Case law in Portuguese decisiones in the Early Modern Age: Antonio da Gama’s Decisiones Supremi Senatus Lusitaniae - Cabral, Gustavo César Machado (2015)
The purpose of this paper is to discuss the role of case law in António da Gama’s (15-15) Decisiones Supremi Senatus Lusitaniae, the first Portuguese book classified as decisiones literature. It is also an object of this paper to clarify how case law was used and its relevance to the structure of the book, as well as describing the information about lawsuits, which was always seen as part of Portuguese and continental European legal framework in the Early Modern Age, is also an objective of this paper.